Pulmonary embolism: incidence and outcomes in a twelve-year historical series, in Tuscany - Italy (2010-2021) - Cerini, Gabriele; Lunetta, Carla; Szasz, Claudia; Misurarca, Leonardo; Gemmi, Fabrizio; Carluccio, Marisa; Lorini, Chiara; Bonaccorsi, Guglielmo; Forni, Silvia (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Pulmonary embolism poses a global health concern. Administrative databases serve as valuable sources for broad epidemiological studies on the prevalence and incidence of major diagnoses or diseases. The primary scope is to provide up-to- date insights into Pulmonary Embolism incidence trends, examining shifts in management and outcomes.Design. This retrospective observational study examines a 12-year dataset from hospitals in the Tuscany Region, covering the first two years of the Covid-19 pandemic. Methods. Administrative data from residents aged 18 and older discharged from hospital between 2010 and 2021 were used for the analysis. Results. Hospitalized pulmonary embolism incidence slightly declined from 2010 to 2019 (64.7 to 60.9 x 100,000; p=0.152). Males under 75 showed a higher incidence rate, while females had higher incidence rates in older age groups. In-hospital and 30-day mortality decreased from 2010 to 2019 (p=0.001 and 0.020 respectively). In 2020, 30-day mortality increased (12.4% vs 10.1%, p=0.029), while in-hospital mortality remained stable. One-year mortality was stable from 2010-2019 but increased in 2020 (32.6% vs 29.4%, p=0.037). Considering the multivariable model, one-year mortality is significantly associated with sex, age, and comorbidities. Conclusions. Our study shows that Pulmonary Embolism persists as a relevant burden in Tuscany region, but with improvements in management over the past decade and a decisive change in pharmacological treatment. Gender-related differences emerge, highlighting the need for a gender-specific healthcare approach.